2005
DOI: 10.1056/nejmoa052399
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 1p and 11q Deletions and Outcome in Neuroblastoma

Abstract: Unb11q LOH and 1p36 LOH are independently associated with a worse outcome in patients with neuroblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
440
3
16

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 517 publications
(493 citation statements)
references
References 24 publications
34
440
3
16
Order By: Relevance
“…The frequently observed GGP tumors are as follows: GGP1a tumors with both 1p loss and MYCN amplification and GGP3s tumors with 11q loss but without MYCN amplification. The former may belong to a typical MYCN-amplified neuroblastoma (White et al, 1995) with a 5-year cumulative survival rate of 42% in our series, whereas the latter to the so-called intermediate type tumor (Srivatsan et al, 1993;Attiyeh et al, 2005) with the rate of 75%. In GGP tumors, it is obvious that MYCN amplification has the most powerful impact on the patient prognosis.…”
Section: Discussionmentioning
confidence: 62%
“…The frequently observed GGP tumors are as follows: GGP1a tumors with both 1p loss and MYCN amplification and GGP3s tumors with 11q loss but without MYCN amplification. The former may belong to a typical MYCN-amplified neuroblastoma (White et al, 1995) with a 5-year cumulative survival rate of 42% in our series, whereas the latter to the so-called intermediate type tumor (Srivatsan et al, 1993;Attiyeh et al, 2005) with the rate of 75%. In GGP tumors, it is obvious that MYCN amplification has the most powerful impact on the patient prognosis.…”
Section: Discussionmentioning
confidence: 62%
“…The 1p36 region is frequently lost in neuroblastoma and gliomas, implicating CAMTA1 as a tumor suppressor gene. 11,12 Most cases with classic morphology (ie, lacking mature vascular channel formation) examined so far contain this translocation, 8,9 which is not directly targetable with present day therapeutics, but may reveal downstream targets in future studies.…”
Section: Geneticsmentioning
confidence: 99%
“…Deletions affecting the long arm of chromosome 11 mark a subgroup of near diploid tumors which, despite mostly being MYCN nonamplified, show a poor prognosis (Attiyeh et al, 2005). aCGH analysis showed that the CCND1 locus at chromosomal band 11q13 is proximal of these deletions and never lost.…”
Section: Aberrations Of Ccnd1-cdk Complex Genes In Neuroblastomamentioning
confidence: 99%